Outcome of primary posterior tracheopexy in thoracoscopically repaired esophageal atresia neonates with tracheomalacia; single center's experience - Mohamed M. Elbarbary; Basma Magdy; Mahmoud ElFiky; Ahmed M.K. Wishahy; Ayman Hussein; Maggie L Naguib; Mohamed Elseoudi (Elsevier, 2023)
Background: Tracheomalacia frequently develops in esophageal atresia patients (EA) especially in those with tracheoesophageal fistula (TEF). Conservative management has been the standard treatment; however, it was reported that delay in management could result in chronic lung conditions. Thus, early surgical interventions have been recently recommended. Patients and Methods: We enrolled patients presented with type-C esophageal atresia, with concomitant moderate to severe tracheomalacia, who had their thoracoscopic intervention done during the study period 2019-2022. Early and intermediate- term outcomes were studied and compared to another cohort with mild or no tracheomalacia. Results: During the allocated study period, 24 patients met the inclusion criteria for tracheopexy, but only 17 were followed up due to early demise of the other seven. During the follow-up period, 7/17 patients developed respiratory symptoms, which were attributed to esophageal stricture in 5 patients, recurrent TEF in 2 patients and one of them had residual tracheomalacia in addition to the developed recurrent TEF. The outcomes of the enrolled patients for tracheopexy were similar to those with no or mild tracheomalacia. Conclusions: Primary posterior tracheopexy during the primary repair might be considered a safe and feasible option not only to alleviate respiratory symptoms secondary to tracheomalacia in EA patients, but also to decline the need of further surgical interventions. However, more comprehensive studies with long-term follow-ups are mandatory.